Polarization Sensitive Reflection and Dielectric Spectra in GaSe Thin Films. (31st July 2016) - Khanfar, Hazem K.; Qasrawi, Atef A.
Abstract : The light polarization effects on the optical reflective and dielectric spectra of GaSe thin films are studied in the incident light wavelength range of 200–1100 nm. In this range of measurement, the angle of incidence (θ i ) of light was varied between 30° and 80°. In addition, atθ i of 30° the light polarizing angle (δ ) was altered in the range of 0–90°. Regardless of the value ofλ, for allθ i ≻ 6 5 °, the total reflectance sharply decreased with increasingθ i . In addition, whenθ i is fixed at 30° andδ was varied, the amplitudes ratio of the polarized waves exhibits a resonance-antiresonance phenomenon at a wavelength that coincides with the film's thickness (800 nm). This behavior was assigned to the coupled interference between incident and reflected waves and to the strong absorption effects. Two main resonance peaks are observed as response tos -polarized and normal incident beam: one is at ~540 (556 nm) and the other at ~420 THz (714 nm). The dielectric constant of the GaSe films exhibits anisotropic characteristics that nominate it for use as multipurpose optoelectronic devices.